Physiological and Biochemical Analyses Shed Light on the Response of Sargassum vulgare to Ocean Acidification at Different Time Scales - Kumar, Amit; AbdElgawad, Hamada; Castellano, Immacolata; Lorenti, Maurizio; Delledonne, Massimo; Beemster, Gerrit T. S.; Asard, Han; Buia, Maria Cristina; Palumbo, Anna (Frontiers in Plant Science, 2017)
Studies regarding macroalgal responses to ocean acidification (OA) are mostly limited to short-term experiments in controlled conditions, which hamper the possibility to scale up the observations to long-term effects in the natural environment. To gain a broader perspective, we utilized volcanic CO2 vents as a “natural laboratory” to study OA effects on Sargassum vulgare at different time scales. We measured photosynthetic rates, oxidative stress levels, antioxidant contents, antioxidant enzyme activities, and activities of oxidative metabolic enzymes in S. vulgare growing at a natural acidified site (pH 6.7) compared to samples from a site with current pH (pH 8.2), used as a control one. These variables were also tested in plants transplanted from the control to the acidified site and vice-versa. After short-term exposure, photosynthetic rates and energy metabolism were increased in S. vulgare together with oxidative damage. However, in natural populations under long-term conditions photosynthetic rates were similar, the activity of oxidative metabolic enzymes was maintained, and no sign of oxidative damages was observed. The differences in the response of the macroalga indicate that the natural population at the acidified site is adapted to live at the lowered pH. The results suggest that this macroalga can adopt biochemical and physiological strategies to grow in future acidified oceans.